STANY ZJEDNOCZONE JAKO KOLEBKA NOWOCZESNEGO PRAWA ADOPCYJNEGO - Łukasiewicz, Rafał (Zeszyty Prawnicze, 2016)
The aim of this article is to present the origin of modern adoption law in the USA, which marked a quantum leap in the field of adoption. The author writes about the circumstances in which the innovative Massachusetts Adoption of Children Act came into force in 1851. The main reason for the introduction of this legislation was the American model of the family, which was different from the European practice. The strength of the typical American family was assessed on the basis of the number of individuals in it, while in Europe families tried to keep their estate in the hands of as few individuals as possible. By the early 1900s informal adoption had become widespread in the USA, and families wanted adoption to be given a legal status. This period was also marked by the beginning of the Orphan Train Movement for the placement of orphaned, homeless, and abandoned children in foster families in the West of the United States. This phenomenon in social welfare may be regarded as a second reason prompting the development of US adoption law. The article explains why the Massachusetts Adoption of Children Act was so important for the development of adoption law. This legislation provided a model for our present-day concept of the purpose of adoption – a child’s welfare. In 19th-century European law adoption was an institution serving only parents’ interests and it was considered part of inheritance law, rather than of family law. Under the Adoption of Children Act an adoption had to be right for the welfare of the child, and adoptive parents had to be emotionally and materially ready for their new social role. The Polish literature on law presents these issues only in a brief way, so it may be interesting to show how important the 1851 Adoption of Children Act is for current law.